TAX AMNESTY APPLICATION ON TAX OBJECTS THAT BECAME DISPUTES IN THE COURT IN INDONESIA - Rochmi Tisnavianti; Herini Siti Aisyah (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
The procedure for filing a tax amnesty application in the Tax amnesty program has been regulated in Act Number 11 of 2016 concerning Tax Amnesty, General Provision and Tax Procedures (KUP) Law. However, tax objects that are still in dispute in the court have different procedures and not regulated in detail in the legislation. Due to this reason, this study aims to examine tax amnesty application on tax objects that are disputed in court in Indonesia. This study used a normative legal approach which was conducted by the study of literature and documentation of legislation and policies relating to theories and principles of tax law, especially tax amnesty policies. The results showed that tax amnesty in the case of a tax object that is still in the process of dispute can be performed by the withdrawal of the lawsuit; the trial process is suspended until the issuance of a statement. Thus, it can be concluded that the application for tax amnesty related to the dispute object has its own rules and conditions which are supervised directly by the Director General of Taxes and the Ministry of Finance.